Erythema elevatum diutinum as a first clinical manifestation for diagnosing HIV infection: case history - Rover, Patrícia Accioni; Bittencourt, Caroline; Discacciati, Mariana Pimenta; Zaniboni, Mariana Colombini; Arruda, Lúcia Helena de Fávaro; Cintra, Maria Letícia (São Paulo Medical Journal, 2005)
CONTEXT: Erythema elevatum diutinum is a chronic and rare dermatosis that is considered to be a variant of leukocytoclastic vasculitis. It is probably mediated by immune complexes. It is generally associated with autoimmune, neoplastic and infectious processes. Recently, it has been added to the group of specific dermatoses that are associated with HIV. CASE REPORT: We report on the case of a patient who had erythema elevatum diutinum as the first clinical evidence for diagnosing HIV infection. Dapsone was used in the treatment of this patient, and partial regression of the lesions was achieved within 15 days, even before anti- retroviral therapy was prescribed. CONCLUSION: When there is a diagnosis of erythema elevatum diutinum, HIV infection should be investigated, especially in atypical and exacerbated clinical manifestations.